Chicken Pleiotrophin: Regulation of Tissue Specific Expression by Estrogen in the Oviduct and Distinct Expression Pattern in the Ovarian Carcinomas - Lee, Jin-Young; Jeong, Wooyoung; Lim, Whasun; Kim, Jinyoung; Bazer, Fuller W.; Han, Jae Yong; Song, Gwonhwa (PLOS ONE, 2012)
Pleiotrophin (PTN) is a developmentally-regulated growth factor which is widely distributed in various tissues and also detected in many kinds of carcinomas. However, little is known about the PTN gene in chickens. In the present study, we found chicken PTN to be highly conserved with respect to mammalian PTN genes (91–92.6%) and its mRNA was most abundant in brain, heart and oviduct. This study focused on the PTN gene in the oviduct where it was detected in the glandular (GE) and luminal (LE) epithelial cells. Treatment of young chicks with diethylstilbesterol induced PTN mRNA and protein in GE and LE, but not in other cell types of the oviduct. Further, several microRNAs, specifically miR-499 and miR-1709 were discovered to influence PTN expression via its 3′-UTR which suggests that post-transcriptional regulation influences PTN expression in chickens. We also compared expression patterns and CpG methylation status of the PTN gene in normal and cancerous ovaries from chickens. Our results indicated that PTN is most abundant in the GE of adenocarcinoma of cancerous, but not normal ovaries of hens. Bisulfite sequencing revealed that 30- and 40% of −1311 and −1339 CpG sites are demethylated in ovarian cancer cells, respectively. Collectively, these results indicate that chicken PTN is a novel estrogen-induced gene expressed mainly in the oviductal epithelia implicating PTN regulation of oviduct development and egg formation, and also suggest that PTN is a biomarker for epithelial ovarian carcinoma that could be used for diagnosis and monitoring effects of therapies for the disease.